Microscopic Visualization of Cell-Cell Adhesion Complexes at Micro and Nanoscale - Vanslembrouck, Bieke; Chen, Jian-hua; Larabell, Carolyn; van Hengel, Jolanda (Frontiers in Cell and Developmental Biology, 2022)
Considerable progress has been made in our knowledge of the morphological and functional varieties of anchoring junctions. Cell-cell adhesion contacts consist of discrete junctional structures responsible for mechanically coupling cytoskeletons and allowing the transmission of mechanical signals across a cell collective. The three main adhesion complexes are adherens junctions, tight junctions, and desmosomes. Microscopy has played a fundamental role in understanding these adhesion complexes on different levels both in physiological and pathological conditions. In this review, we will discuss the main light microscopy and electron microscopy techniques used to unravel the (i) structure and (ii) composition of the three cell-cell contacts in epithelial and endothelial cells. It functions as a guide to pick the appropriate imaging technique for the adhesion complexes of interest. We will also point out the latest techniques that have emerged. At the end, we discuss some limitations of the new developments, and the problems investigators encounter during their research using microscopic techniques.